Development of indicator system for early warning of clinical nursing critical values in general wards: a Delphi study - Weixin Xiong; Fenglan Xie; Qin Li; Ying Chen; Hongmei Yang; Jieli Wu; Jianying Li; Zhihao Chen; Xiaoqin Hu; Lijing Hu (BMC Nursing)
Abstract Aim This study aimed to develop an indicator system for early warning of clinical nursing critical values for implementation in general wards. Background By simultaneously assessing multiple physiological parameters, subtle changes in a patient’s clinical status can be more readily identified. However, the literature indicates that current early warning systems (EWS) are primarily utilized in in critical care units (ICU), prehospital first aid and hospital emergency cases. There remains a lack of consensus regarding early warning systems for critical nursing values in general wards, along with a shortage of effective and practical quantitative indicators for nursing risk prevention. Methods This study employed an integrative research approach combining literature review, theoretical analysis, and qualitative methodology. Through systematic screening, a critical nursing value warning indicators draft was identified. two-round Delphi survey was conducted involving 148 experts from clinical nursing, nursing education, and professional associations. The entire research process strictly adhered to the modified Conducting and Reporting of Delphi Studies (CREDES) guidelines and the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) checklist to ensure methodological rigor and transparency. Results In the two Delphi survey rounds, the response rates for the two questionnaires were 96.62% and 99.32%, respectively. The authority coefficients were 0.854 and 0.871, respectively, with coefficients of variation ranging from 0.08 to 0.23. The final early warning system for clinical nursing critical values in general wards was composed of 10 primary indicators and 23 secondary indicators. Conclusions The developed indicator system for clinical nursing critical value early warning in general wards demonstrates both scientific reliability and practical applicability. It provides clear guidance to clinical nurses, enabling timely detection of patient condition changes, prevention of adverse events, and assurance of clinical nursing safety. Implications for nursing management The development and establishment of indicator system for early warning of clinical nursing critical values in general wards will help to identify changes in patient conditions, avoidance of adverse events, and the assurance of clinical nursing safety.